QoS-aware routing protocol using adaptive retransmission of distorted descriptions in MDC for MANETs. (2018) - Bhardwaj, Diwakar; Kant, Krishna; Chauhan, Durg Singh
Quality of service (QoS) of delay sensitive application like video stream is majorly affected by instantaneous channel conditions over noisy mobile ad-hoc networks (MANETs). Methods like forward error correction (FEC) and automatic repeat request (ARQ), multiple description coding (MDC), and MDC with error correction (MDC_EC) design to recover the quality of the video in noisy wireless networks under perform in MANETs because of their high overheads and high retransmission delay. MDC and MDC_EC produce unacceptable video quality at the receiver and fail to fulfil the QoS requirements of the video applications. We have proposed a novel routing protocol to support QoS and reduce overheads. The proposed work is twofold: i) redefine the distortion model to estimate the distortion of the transmitted video; ii) proposed a novel routing protocol model to mitigate the impact of channel noise on the video quality through selected retransmission of noisy descriptors (MDC_EC_RE).